Kinematics analysis of a new parallel robotics. (27th April 2020) - Baoyu, Shi; Hongtao, Wu
A new type of parallel robot ROBO_003 is presented. Its mechanisms, kinematics, and virtual prototype technology are introduced. The research of degrees of freedom (DOF) is based on screw theory, a set of screw is separated as a branch, which named as constrain screw. The type of three DOF gained by counting constrain screw, the moving platform's frame, and base platform's frame is set, respectively, a complete kinematic research including closed-form solutions for direct kinematic problem. The 3-D model of ROBO_003 is established using SOLIDWORKS; position and orientation of motion platform can be gained using ADMAS, which is a type of virtual prototype technology. The resultant shows that the structure of ROBO_003 is reasonable, three DOF of motion platform can be operated in a reasonable range, the solutions to the direct kinematics are right, and robot ROBO_003 can be used in many industrial fields. The research of this article provides a basis for the practical application of parallel robotics ROBO_003.